The Influence Of Disruptive Innovation, Organisational Capabilities And People On Organisational Performance: Strategic Agility As Mediator - Koay, Hooi Gee (2021)
The purpose of this research is to examine the influence of disruptive innovation, organisational capabilities, and people on organisational performance. It also examines the mediating influence of strategic agility on the relationship between disruptive innovation, organisational capabilities, people, and organisational performance. A quantitative study was designed, 121 responses were collected among electrical & electronics (E&E) manufacturing organisations in Malaysia. The study utilised structured questionnaires via a purposive sampling technique. The data collected were analysed using SPSS and SmartPLS. The result showed that disruptive innovation, organisational capabilities, and people have a significant influence on strategic agility, which in turn has a significant influence on organisational performance. Strategic agility also mediates the relationship between disruptive innovation, organisational capabilities, and people and organisational performance. From the academic aspect, the conceptual framework formulated is based on research gap, I-TOP strategic agility model, and dynamic capabilities theory that provides more insight on how to optimise organisational performance. In recent years, countries have been utilising the happiness index as the measurement of economic growth instead of solely on GDP. This study measured the organisational performance through employee, customer and shareholder happiness. Practitioners can utilise the findings of this research to formulate a more effective strategy to optimise their organisational performance that is crucial for business sustainability.